2018
DOI: 10.1186/s12889-018-5126-1
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and subjective wellbeing of non-compliant mothers to childhood oral polio vaccine supplemental immunization in Northern Nigeria

Abstract: BackgroundAttitude and subjective well-being are important factors in mothers accepting or rejecting Oral Polio Vaccine (OPV) supplemental immunization. The purpose of the study was to determine the role of mothers’ attitude and subjective wellbeing on non-compliance to OPV supplemental immunization in Northern Nigeria.MethodsThe study utilized a cross-sectional design to assess attitude and subjective well-being of mothers using previously validated VACSATC (Vaccine Safety, Attitudes, Training and Communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…From what was observed in this study, the government in collaboration with development partners and experts should support the conduct of operational studies to fully understand factors that may be responsible for noncompliance in addition to what was outlined here, earlier observed by Umeh et al, (2018). Addressing these issues could, therefore, be key to eliminating polio and other diseases of public health importance (Svea et al, 2015).…”
Section: Results:-demographic Characteristics Of Respondersmentioning
confidence: 66%
“…From what was observed in this study, the government in collaboration with development partners and experts should support the conduct of operational studies to fully understand factors that may be responsible for noncompliance in addition to what was outlined here, earlier observed by Umeh et al, (2018). Addressing these issues could, therefore, be key to eliminating polio and other diseases of public health importance (Svea et al, 2015).…”
Section: Results:-demographic Characteristics Of Respondersmentioning
confidence: 66%
“…Having expectation towards the protection that follows childhood immunization signi cantly in uence childhood immunization [52]. Likewise, Knowing the seriousness of VPDs was also found to be a predictor for non-compliance [41]. The more knowledge mothers acquired with regards to bene t of child immunization and consequences of not immunizing a child the more tendency of increasing their practice con dence towards childhood immunization uptake.…”
Section: Maternal Outcome Expectationsmentioning
confidence: 88%
“…With regards to maternal outcome expectation, three studies reported knowledge on bene t of childhood immunization uptake [29,30,52] and one study revealed severity of VPDs [41]. For environmental factors, two studies reported religious belief [40,64].…”
Section: Modi Able Factorsmentioning
confidence: 99%
“…Vaccines save lives and confer herd immunity that breaks the transmission of vaccine preventable diseases in communities [10] . Vaccine hesitancy is on the rise in developed and developing countries, making delivery of potent vaccines to at risk population, mostly children difficult [11] , [12] , [13] . But developing countries, like Nigeria, face more challenges in addition to the low demand for vaccines; weak infrastructure, crippling poverty, inadequate planning and low premium on health [6] , [9] .…”
Section: Introductionmentioning
confidence: 99%